Internal loss of AlGaN-based ultraviolet-B band laser diodes with p-type AlGaN cladding layer using polarization doping. (29th June 2020) - Omori, Tomoya; Ishizuka, Sayaka; Tanaka, Shunya; Yasue, Shinji; Sato, Kosuke; Ogino, Yuya; Teramura, Shohei; Yamada, Kazuki; Iwayama, Sho; Miyake, Hideto; Iwaya, Motoaki; Takeuchi, Tetsuya; et al.
Abstract: Aluminum gallium nitride (AlGaN)-based ultraviolet-B band laser diodes (LDs) with a p-type AlGaN cladding layer using polarization doping were fabricated on lattice-relaxed Al0.6 Ga0.4 N/AlN/sapphire. The threshold current density J th and lasing wavelength of this LD were 25 kA cm −2 and 298 nm, respectively. The internal loss ( α i ) was estimated by means of a variable stripe length method using optical excitation. The α i value of this LD was relatively low (i.e. <10 cm −1 ), thus suggesting that the device is characterized by both, proper light confinement and low internal loss.